THE TEACHING OF ENGLISH AT JUNIOR HIGH SCHOOL - Ayu - Wandyra (Language-Edu, 2020)
This study aimed to describe  the objective condition about how the teaching of English at Junior High School, this study is focused on the instructional materials, the instructional activities, the assessment the teacher used to measure the students’ achievement and how the students’ achievement is, and the teacher evaluates the students. In this study, the researcher used a descriptive qualitative research design. The researcher collected the data through observation, interviews and documentation. The finding of this study showed that the teacher used the one instructional material and the various kinds of supplementary materials. The supplementary materials are selected by the teacher to become the interesting materials; it also suitable for the students. In the instructional activities, teacher presented the four skills and language components in the teaching and learning activities; the teacher always has given reward to the students who answer her question. The assessment was carried out by the teacher using 2 methods which are direct and not directly. The students’ achievemvent increase since the teacher applied the good practices. Next, the teacher evaluated the students by using process evaluate. summative evaluate was the evaluation of the students progress after the teaching of English process in the classroom.